What Is a Mathematical Exhibition? (Revista de Cultura e Extensão USP, 2015)
This article begins by discussing what is expected of a math exhibition and describes the work of Matemateca’s team over approximately ten years in forming a collection of mathematical objects in the Instituto de Matemática e Estatística da USP. It also describes the evolution of the underlying concept of this exhibition aimed at the general public, but focused on students of all levels. Several examples of exhibits are given as well as some possible approaches to attract the visitor. It is also given an overview of the international scene with respect to mathematical exhibitions to allow the reader to place the Matemateca in this context. Finally, some paths are considered for the continuity and improvement of this work.